2018
DOI: 10.18203/2349-3933.ijam20181844
|View full text |Cite
|
Sign up to set email alerts
|

Changing clinical profile of malaria at a tertiary care hospital

Abstract: Background: There is a widespread range of diverse typical and atypical manifestations of malaria. The diagnosis of malaria may escape the attention of treating physician due to its unusual and vague presentations.The morbidity and mortality due to malaria is increased due to lack of early diagnosis and right treatment. The Aim of the present study was to examine the changing clinical pattern of malaria with special attention to atypical presentations.Methods: The present study comprised of 630 cases of defini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 5 publications
1
7
3
Order By: Relevance
“…In Khuraiya P et al, study chills and rigors was present in 90.3% of patients, In Kalavati GP et al, study chills and rigors was observed in 84.8%, in Rathod SN et al, study group it was Observed in 83.1% of patients. 9,11,14 But in Surve KM et al, study group it was observed in only 64% of patients which showing lower incidence of chills and rigors when compared to this study. 8 It was also noted that 27% of the patients had easy fatiguability as their presenting complaint.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…In Khuraiya P et al, study chills and rigors was present in 90.3% of patients, In Kalavati GP et al, study chills and rigors was observed in 84.8%, in Rathod SN et al, study group it was Observed in 83.1% of patients. 9,11,14 But in Surve KM et al, study group it was observed in only 64% of patients which showing lower incidence of chills and rigors when compared to this study. 8 It was also noted that 27% of the patients had easy fatiguability as their presenting complaint.…”
Section: Discussioncontrasting
confidence: 53%
“…52.4% and 52.88% respectively. 14,11 In other study groups like Surve KM et al, Patel G et al, Kalavati GP et al, and Anshika Jain et al, incidence of vomiting is lower compared to this study. In Anshika jain et al, study group it was 31.84%, Kalavati GP et al group it was 37.1% and in Patel GI group it was 33%.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations